(untitled) (Tzintzun, Revista de Estudios Históricos, 2016)
This article analyzes the content of the public, political and intellectual discourse, on the indigenous groups along the history of México an independent country to the 2000. In this work we propose that the assignment of indigenous identities across the public speech answers to the needs of self perception, self identification and the construction of the State. This State creates ethnic identities according to the historical moment, aiming to construct the national project. In this present investigation there will be four types of discourse analyzed through the nineteenth and twentieth century, in which substantial changes are made in the rhetoric of the national project, and when also variations in the way of perceiving, defining and describing indigenous groups occurred. In spite of the assumed changes, through the research, it is acknowledge that certain continuities prevail and remain.